PENGARUH CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DALAM MEMILIH MINUMAN PENGGANTI ION TUBUH / ISOTONIK MEREK MIZONE - Desi Anggraini; Desi Tri Kurniawati (Jurnal Ilmiah Mahasiswa FEB, 2012)
Intense competition between companies is now also occurs in isotonic beverage company. Initially aligned with isotonic drink soft drinks or even with mineral water, But in reality is very different from the isotonic drink the beverage products.  Isotonic drinks are beverages ion replacement body for health and fitness. As an isotonic beverage pioneer PT Aqua Danone with Mizone products ceaselessly to educate the market. Rhis study aims to analyze the variables comprising the brand image of the image of the product, image  user, image makers who influence purchase decisions mizone brand isotonic drinks to students of economics and business faculty University of Brawijaya MalangKeywords : brand image, consumer purchasing decisions